Acute Kidney Injury by Radiographic Contrast Media: Pathogenesis and Prevention - Michele Andreucci (BioMed Research International, 2014)
It is well known that iodinated radiographic contrast media may cause kidney dysfunction, particularly in patients with preexisting renal impairment associated with diabetes. This dysfunction, when severe, will cause acute renal failure (ARF). We may define contrast-induced Acute Kidney Injury (AKI) as ARF occurring within 24–72 hrs after the intravascular injection of iodinated radiographic contrast media that cannot be attributed to other causes. The mechanisms underlying contrast media nephrotoxicity have not been fully elucidated and may be due to several factors, including renal ischaemia, particularly in the renal medulla, the formation of reactive oxygen species (ROS), reduction of nitric oxide (NO) production, and tubular epithelial and vascular endothelial injury. However, contrast-induced AKI can be prevented, but in order to do so, we need to know the risk factors. We have reviewed the risk factors for contrast-induced AKI and measures for its prevention, providing a long list of references enabling readers to deeply evaluate them both.